2020
DOI: 10.1097/md.0000000000023872
|View full text |Cite
|
Sign up to set email alerts
|

Decreased albumin is associated with elevated N-terminal pro-brain natriuretic peptide and poor long-term prognosis in patients with chronic heart failure

Abstract: At present, the association between albumin, N-terminal pro-brain natriuretic peptide (NT-proBNP) and long-term prognosis in patients with chronic heart failure (CHF) is unclear. Therefore, the purpose of this study is to explore the relationship between albumin, NT-proBNP and all-cause mortality in CHF patients. Three hundred fifty two CHF patients were recruited in our study, and patients were divided into 2 groups according to the mean (37.16 g/L) of albumin concentration [low group (albumin < 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Meanwhile, the declined serum albumin has been evidenced to be associated with many adverse cardiovascular or cerebrovascular events, including HF, atrial fibrillation, infective endocarditis and stroke. 56 Consistent with a previous study in patients with chronic HF, 57 our results demonstrated that decreased albumin was linked to elevated NT-pro-BNP in bedridden patients with stroke. ROC curve analysis showed that serum albumin with a cut-off value of 37.15 g/L may be an important factor for high levels of NT-pro-BNP in bedridden patients with stroke.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, the declined serum albumin has been evidenced to be associated with many adverse cardiovascular or cerebrovascular events, including HF, atrial fibrillation, infective endocarditis and stroke. 56 Consistent with a previous study in patients with chronic HF, 57 our results demonstrated that decreased albumin was linked to elevated NT-pro-BNP in bedridden patients with stroke. ROC curve analysis showed that serum albumin with a cut-off value of 37.15 g/L may be an important factor for high levels of NT-pro-BNP in bedridden patients with stroke.…”
Section: Discussionsupporting
confidence: 91%
“…Low albumin levels in hospitalized patients at the time of admission are associated with increased short-and long-term mortality rates [4]. Previous studies have shown significant associations of hypoalbuminemia with increased cardiovascular morbidity and mortality [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…D-dimer was related to thrombosis, which contributes to the adverse events of HF 33–35 44. (2) The lower albumin in HF aggravates congestion, leading to lower intravascular colloid osmotic pressures, an increase of systematic oxidant stress and the tendency to infections 32 45 46. Therefore, albumin is a summation of several risk factors of poor outcomes.…”
Section: Discussionmentioning
confidence: 99%